Distributed sampled‐data containment control of linear multi‐agent systems with fixed topology. Issue 14 (1st September 2017) - Zhang, Wenbing; Wang, Zidong; Liu, Yurong; Ding, Derui; Alsaadi, Fuad E.
Abstract : This study investigates the sampled‐data containment control problem for linear multi‐agent systems with multiple leaders under undirected or directed network topology. First, by means of the decomposition method, the containment control problem is transformed into the simultaneous stability analysis issue of certain subsystems. Then, the solution of a class of differential equations, which plays a key role for the addressed problem, is exploited by using the contradiction method. Together with a novel Lyapunov function, sufficient conditions are established to guarantee that all the followers move into the convex hull spanned by the leaders. The proposed results are dependent on the information of the system dynamics, the coupling strength as well as the eigenvalues of topology matrix. Furthermore, the established results are specialised to both the leader–following case and the traditional consensus case. Finally, simulations are given to illustrate the theoretical results derived in this study.